To sleep, or not to sleep – that is the question, for polysomnography. Issue 2 (June 2017) - Corlateanu, Alexandru; Covantev, Serghei; Botnaru, Victor; Sircu, Victoria; Nenna, Raffaella
As the English dramatist Thomas Dekker wrote, "Sleep is that golden chain that ties health and our bodies together". One of the most frequently sleep-related disorders (SRD) is obstructive sleep apnoea syndrome (OSAS). OSAS is a relatively "young" disease and at the same time, one of the most important respiratory conditions discovered in the last 50 years due to its incidence, prevalence, health-related impact on the patient's life and economic burden [1]. Have we reached the point where respiratory polygraphy can replace polysomnography in the assessment of OSAS? http://ow.ly/UxCU30bNopq